2020
DOI: 10.1101/2020.10.02.324285
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The X-linked intellectual disability gene product and E3 ubiquitin ligase KLHL15 degrades doublecortin proteins to constrain neuronal dendritogenesis

Abstract: Proper brain development and function requires finely controlled mechanisms for protein turnover and disruption of genes involved in proteostasis is a common cause of neurodevelopmental disorders. Kelch-like 15 (KLHL15) is a substrate adaptor for cullin3 (Cul3)-containing E3 ubiquitin ligases and KLHL15 gene mutations were recently described as a cause of severe X-linked intellectual disability. Here, we used a bioinformatics approach to identify a family of neuronal microtubule-associated proteins (MAPs) as K… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
(104 reference statements)
0
1
0
Order By: Relevance
“…35 Ubiquitin-mediated proteolysis comprises 2 steps: the binding of ubiquitin molecules to protein substrates and the degradation of the polyubiquitin proteins by the 26S proteasome complex, which plays an important role in protein degradation, regulation of the cell cycle, modulation of the immune and inflammatory responses, control of signal transduction pathways, development, and differentiation. [36][37][38] Furthermore, many studies have shown that suppressing the ubiquitin-mediated proteolysis pathway promotes the proliferation and migration of tumor cells. [39][40][41] Thus, AS events in patients with bladder cancer might impact a variety of biological functions via the ubiquitin-mediated proteolysis pathway.…”
Section: Discussionmentioning
confidence: 99%
“…35 Ubiquitin-mediated proteolysis comprises 2 steps: the binding of ubiquitin molecules to protein substrates and the degradation of the polyubiquitin proteins by the 26S proteasome complex, which plays an important role in protein degradation, regulation of the cell cycle, modulation of the immune and inflammatory responses, control of signal transduction pathways, development, and differentiation. [36][37][38] Furthermore, many studies have shown that suppressing the ubiquitin-mediated proteolysis pathway promotes the proliferation and migration of tumor cells. [39][40][41] Thus, AS events in patients with bladder cancer might impact a variety of biological functions via the ubiquitin-mediated proteolysis pathway.…”
Section: Discussionmentioning
confidence: 99%